The Implementation of Roleplay Activities to Get Students Speak - Vivit - Rosmayanti; Muhammad Yahrif (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2019)
This study aimed to elaborate the implementation of Role-play activities to get students speak more in the class. The subjects of this research were second grade students of SMA Tutwuri Handayani Makassar which consist of 26 students. This research applied qualitative case study, conducted collaboratively to elaborate the implementation of Role-play activities in English class. The focus of the research were the implementation of role-play activities during the class in relation to how those activities were implemented in the class and some important points in teaching in the class. There are six role-play activities conducted in the class during the research. The six role-play activities are shopping role-play, visiting the doctor role-play, making a phone call role-play, dining out role-play, lost and found role-play, and detective role-play. These role-play activities were considered successful to make students practice more speaking since they were very excited in the class and participate well in every activity. They also become more familiar with English instruction and they practiced speaking more. The result of this research is expected to be useful information for school and teachers in designing teaching activities which are useful for students, and for the researchers to improve the ability in writing scientific paper and solving problems related to educational matter which is exist in society and academic world.